Curricular Innovation: a Look From the Approach of Critical Thinking at School - Cruz Picón, Pablo Emilio (2022)
The curriculum is a dynamic and indissoluble process that plays a significant role for educational entities, since it allows to base and complement education according to the requirements and needs of society and culture. Therefore, this article shows the results of a research process that aimed to determine a proposal for curricular innovation from the critical thinking approach that favors the development of academic and directive management of the school. For this purpose, a qualitative methodology was chosen with an exploratory and descriptive approach. 80% of the population was taken, giving a total of 88 members of the educational community. From primary information and documentary record and data collection instruments, such as the document review matrix, survey, interview and the focus group, it was possible to conclude that a process of curricular foundation that allows the strengthening of critical thinking is given through the development critical skills, mediation, collaborative work and pedagogical transversality.